Fatty acid composition of eggs and semen of Ctenopharyngodon idella (Valenciennes, 1844) taken for culture trials from the Keban Dam Lake, Elazig, Turkey - Harlioglu, A. G. (Wiley, 2015)
[Abstract Not Available]
Keywords: Quality